The Role of the Religious Harmony Forum (FKUB) in Promoting Interfaith Tolerance: Peran Forum Kerukunan Umat Beragama (FKUB) dalam Mewujudkan Toleransi Antarumat Beragama - Nurva Dillatul Vatin; Heru Triasnawa (Institut Agama Islam Sumatera Barat Pariaman, 2026)
Forum Kerukunan Umat Beragama (FKUB), located in Bukittinggi, plays an important role in preventing and addressing potential interreligious conflicts. The organization has been widely recognized for its active efforts in promoting social harmony and strengthening unity among different religious communities through various outreach and educational programs. These initiatives are aimed at fostering peaceful and harmonious relations within the city’s diverse society. In recognition of its dedication and contribution to maintaining religious harmony, FKUB Bukittinggi was awarded the Harmony Award in 2017. This research aims to describe the role of FKUB in promoting interreligious tolerance in Bukittinggi City. The study employs a qualitative method with a literature study approach. The findings show that FKUB Bukittinggi has several roles in fostering religious tolerance, namely: (1) resolving religious conflicts during religious celebrations, (2) maintaining harmony through interfaith activities, (3) conducting dialogues on religious moderation with interfaith leaders in Bukittinggi, and (4) socializing interfaith programs and policies.